(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper presents a low cost, less human effort and low power consumption implementation of smart post box system through the interaction of hardware kit with android application and web application. Whenever the sender wants to drop a letter into the post-box he can either press the open button on the post-box the disc will come out and the sender will put the letter into that disc, and presses the close button. Ultrasonic sensor will detect the letter. When the close button is pressed the letter will be put into the back compartment of the post-box and a notification will be given to the admin that a letter has been dropped in the post-box. It also tells the number of letter that has been dropped into that post-box in the entire day. Then, the postman goes to only that post-box that will be having letters. Now the postman can generate a QR code for each letter by entering sender’s and receiver’s information on the webpage. With the help of that QR code the letter can be traced. Here MySQL database is used to store the data. Data in sense it stores the count of the letters that are present in letter box and the address from where the letter has been received.